DIAGNOSTIC AND INTERVENTIONAL CORONARY PROCEDURES USING DISTAL RADIAL ARTERY IN ANATOMICAL SNUFF BOX: INITIAL EXPERIENCE AT OUR CENTRE - Butt, Faraz Ahmad; Khan, Muhammad Nadir; Jamil, Sadiqa; Rehman, Atiq Ur; Akbar, Muhammad Shoaib; Danyal, Shoaib Muhammad (Pakistan Armed Forces Medical Journal, 2019)
Objective: To evaluate the safety and effectiveness of the dTRA from both the right and left arm. Study Design: Prospective longitudinal study. Place and Duration of Study: The study was conducted in Army Cardiac Centre, Lahore Pakistan, from Nov 2018 to Dec 2018. Methodology: Forty-five consecutive patients who were undergoing coronary angiography/angioplasty were included regardless of indication. Right dTRA was used in 22 patients and left dTRA was used in 20 patients. Procedural success was defined as ability to complete the procedure without conversion to different access site due to failure of coronary artery cannulation. Radial artery patency was checked with doppler ultrasonography both at forearm and snuff box 24 h after successful hemostasis by manual method. We monitored for bleeding and ischemic complications and failure of hemostasis while hospitalization. Results: Procedure was successful in 42 cases (93.3%), 22 (52.3%) diagnostic and 20 (47.6%) coronary intervene-tional procedures, 22 (52.3%) cases from right dTRA and 20 (47.6%) cases from left dTRA. 3 (6.6%) cases were unsuccessful because of weak pulse/hypoplastic distal radial artery or vessel spasm. Manual hemostasis was applied in all cases. There were no ischemic or bleeding complications. No distal or forearm radial artery occlu-sion (RAO) was observed on doppler ultrasonography 24 h after successful hemostasis. Conclusion: dTRA is a safe and feasible radial arterial access which is comfortable for both operator and patient and especially left dTRA provides improved operator ergonomics. Also despite longer time to access distal radial artery and a steeper learning curve, dTRA is a reproducible procedure for coronary interventions in a radial experienced catheterization lab.